Marbling Texture Does Not Affect Muscle Fiber Type of Beef Strip Loin Steaks - E. A. Rice; K. R. Vierck; J. M. Gonzalez; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:Determine the effects of marbling texture and meat quality on muscle fiber type and size. Study Description:Top Choice, Low Choice, and Select beef strip loins (n = 117; 39/grade) were visually categorized into fine, medium, or coarse marbling textures. The strip loins were fabricated into 1-inch steaks. The second steak was used for histology analysis. From each steak four marbling flecks and their surrounding tissue were collected. For each marbling fleck, 1 cryosection was collected for immunohistochemical analysis to determine muscle fiber characteristics. The Bottom Line:These results reveal marbling texture did not impact muscle fiber cross-sectional area. Any potential difference in tenderness with varying marbling texture is not due to muscle fiber cross-sectional area or fiber type.
Keywords: beef; marbling texture; muscle fiber; quality grade